Derivation and External Validation of a Scoring System for Predicting Fracture Risk After Ischemic Stroke in a Canadian Cohort - Smith, Eric E. (JAMA Neurol, 2019)
IMPORTANCE: The risk for low-trauma fracture is increased by more than 30% after ischemic stroke, but existing fracture risk scores do not account for history of stroke as a high-risk condition. OBJECTIVE: To derive a risk score to predict the probability of fracture within 1 year after ischemic stroke and validate it in a separate cohort. DESIGN, SETTING, AND PARTICIPANTS: Prognostic study of a cohort from the Ontario Stroke Registry, a population-based sample of adults in Ontario, Canada, who were hospitalized with ischemic stroke from July 1, 2003, to March 31, 2012, with 1 year of follow-up. A population-based validation cohort consisted of a sample of 13 698 consecutive stroke admissions captured across 5 years: April 2002 to March 2003, April 2004 to March 2005, April 2008 to March 2009, April 2010 to March 2011, and April 2012 to March 2013. EXPOSURES: Predictor variables were selected based on biological plausibility and association with fracture risk. Age, sex, and modified Rankin score were abstracted from the medical records part of the Ontario Stroke Audit, and other characteristics were abstracted from administrative health data. MAIN OUTCOMES AND MEASURES: Incidence of low-trauma fracture within 1 year of discharge, based on administrative health data. RESULTS: The Fracture Risk after Ischemic Stroke (FRAC-Stroke) Score was derived in 20 435 patients hospitalized for ischemic stroke (mean [SD] age, 71.6 [14.0] years; 9564 [46.8%] women) from the Ontario Stroke Registry discharged from July 1, 2003, to March 31, 2012, using Fine-Gray competing risk regression. Low-trauma fracture occurred within 1 year of discharge in 741 of the 20 435 patients (3.6%) in the derivation cohort. Age, discharge modified Rankin score (mRS), and history of rheumatoid arthritis, osteoporosis, falls, and previous fracture were associated with the cumulative incidence of low trauma fracture in the derivation cohort. Model discrimination in the validation cohort (n = 13 698) was good (C statistic, 0.70). Discharge mRS was an important discriminator of risk (relative integrated discrimination improvement, 8.7%), with highest risk in patients with mRS 3 and 4 but lowest in bedbound patients (mRS 5). From the lowest to the highest FRAC-Stroke quintile, the cumulative incidence of 1-year low-trauma fracture increased from 1.3% to 9.0% in the validation cohort. Predicted and observed rates of fracture were similar in the external validation cohort. Analysis was conducted from July 2016 to January 2019. CONCLUSIONS AND RELEVANCE: The FRAC-Stroke score allows the clinician to identify ischemic stroke survivors at higher risk of low-trauma fracture within 1 year of hospital discharge. This information might be used to select patients for interventions to prevent fractures.